How much is too much? The utility of learning materials in online learning - Chua, Xin Fang (2018)
Reinforcement learning is a machine learning method, which is an unsupervised one which situations are mapped to actions. It is to determine the optimal path or method by receiving feedback signal that is also known as the reward. The objective is to find out if more accesses of learning materials would provide with more effective learning. This paper will discuss on one of the reinforcement learning methods, Q Learning, and how this algorithm helps to achieve the objective of the project. It will be explained in the context of a game and a case study. Experimental results are supported together with the theory behind Q Learning.